Should we be concerned about COVID-19 with nonhuman primates? - Santos, Wesley José [UNESP]; Guiraldi, Lívia Maísa [UNESP]; Lucheis, Simone Baldini [UNESP] (Wiley, 2020)
The coronavirus disease 2019 pandemic has radically changed the human activities worldwide. Although we are still learning about the disease, it is necessary that primatologists, veterinarians, and all that are living with nonhuman primates (NHP) be concerned about the probable health impacts as these animals face this new pandemic. We want to increase discussion with the scientific community that is directly involved with these animals, because preliminary studies report that NHP may become infected and develop symptoms similar to those in human beings.
Keywords: coronavirus; disease; monkey; zoo